Cytotoxicity, Genotoxicity and Mutagenicity of Aluminum, Manganese and Lead in Meristematic Cells of Root Allium cepa - Francisco, Luiza Flávia Veiga; Crispim, Bruno do Amaral; Viana, Lucilene Finoto; Nascimento, Hélina dos Santos; Raposo Junior, Jorge Luiz; Grisolia, Alexeia Barufatti (Orbital: The Electronic Journal of Chemistry, 2018)
Metals are chemical contaminants that are not normally biodegradable and accumulate in living organisms. In addition, they may present toxic effects to plants and affect human health causing mutations and adn damage of exposed organisms. The objective of this study was to evaluate the cytotoxicity, genotoxicity and mutagenicity of the aluminum, manganese and lead using A.cepa test. Solutions in three concentrations with the metals and controls were prepared for the genetic analyzes. The seeds of A. cepa were exposed to germination, and evaluation of cytotoxicity, genotoxicity and mutagenicity. The results showed that the concentrations of the metals did not interfere in the growth of the radicle, but the increase in the concentration of the metals was directly proportional to the increase of the number of seeds germinated. For the mitotic index it was observed that the increase in Al concentration provided the increase of cells in cell division, but for Mn and Pb there was reduction. The metals at the concentrations evaluated did not present genotoxic and mutagenic potential for meristematic cells of A. cepa. The A. cepa test it showed to be effective for performed analyzes, however, further studies are needed using other biological assays. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1037